UMKM Cooperation Agreement with The Retail System (Case Study on MSME Bakti Indonesia with PT. Indomarco Prosmatama/Indomaret Salatiga) - Hilham Fatiha; Moh Indra Bangsawan (Universitas Muhammadiyah Surakarta, 2023)
The aim of the research is to find out how the implementation of cooperation agreements and dispute resolution occurs in the event of default between UMKM BAKTI INDONESIA and PT. Indomarco Pristmatama/INDOMARET. Research uses normative legal research, namely research on legal rules, principles, concepts or doctrines. Involves careful systematic exposition, analysis, and critical evaluation of legal rules, principles or doctrines related to the formulation of the problem. Implementation of the Cooperation Agreement Between UMKM BAKTI INDONESIA and PT. Indomarco Pristmatama/INDOMARET is in accordance with Article 1338 of the Civil Code concerning the principle of freedom of contract and Article 1320 of the Civil Code concerning the legal terms of buying and selling but in practice it still encounters obstacles. The form of settlement in the event of default is as described in 1276 of the Civil Code and through litigation through the District Court. Dispute Resolution If There Is a Default in the Agreement Between UMKM BAKTI and PT. Indomarco Pristmatama/INDOMARET actually did not regulate in writing the form of settlement, but if in the future it does occur it should be resolved in non‐litigation when one party still cannot find an agreement.